2020
DOI: 10.1038/s41467-020-15386-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial contextual effects in primary visual cortex limit feature representation under crowding

Abstract: Crowding is a profound loss of discriminability of visual features, when a target stimulus is surrounded by distractors. Numerous studies of human perception have characterized how crowding depends on the properties of a visual display. Yet, there is limited understanding of how and where stimulus information is lost in the visual system under crowding. Here, we show that macaque monkeys exhibit perceptual crowding for target orientation that is similar to humans. We then record from neuronal populations in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 68 publications
(97 reference statements)
4
35
1
Order By: Relevance
“…Our results seem to be in-line with prior work showing degradation of information when there are multiple stimuli presented (Day and Delgutte 2013;Day et al 2012;Henry and Kohn 2020). If this reduction in information scales with number of stimuli it could potentially explain the finding that the number of distinctly identifiable sounds saturates at three (Zhong and Yost 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our results seem to be in-line with prior work showing degradation of information when there are multiple stimuli presented (Day and Delgutte 2013;Day et al 2012;Henry and Kohn 2020). If this reduction in information scales with number of stimuli it could potentially explain the finding that the number of distinctly identifiable sounds saturates at three (Zhong and Yost 2017).…”
Section: Discussionsupporting
confidence: 92%
“…When the number of objects gets too great, it is unlikely that neurons can fluctuate between all of them, and this is likely to have consequences for perception, perhaps accounting for well-known limits on the number of objects we can perceive, attend to and remember (e.g. Miller, 1956;Whitney and Levi, 2011;Henry and Kohn, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This observation appears to suggest that an increase in objects in a VE may impact the effectiveness of guidance. The reason for this occurrence, may be visual crowding, as objects may become more difficult to differentiate (Whitney and Levi, 2011;Henry and Kohn, 2020). This is often as a result of attention and spatial integration (Henry and Kohn, 2020), in which the distance between objects in an environment are crucial for being able to identify a target object (Bouma, 1970;Whitney and Levi, 2011;Melnik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this occurrence, may be visual crowding, as objects may become more difficult to differentiate (Whitney and Levi, 2011;Henry and Kohn, 2020). This is often as a result of attention and spatial integration (Henry and Kohn, 2020), in which the distance between objects in an environment are crucial for being able to identify a target object (Bouma, 1970;Whitney and Levi, 2011;Melnik et al, 2020). Although this study did not infer the attractors as a target object, participants may have identified this as a target object within the VE, however visual crowding may have occurred when placing more objects into the VE, making it more difficult to identify the attractors as a target object.…”
Section: Discussionmentioning
confidence: 99%